IDENTIFIKASI BAKTERI Salmonella sp. PADA IKAN TONGKOL LISONG (Auxis rochei) ASAP DI SENTRAL IKAN ASAP KABUPATEN PROBOLINGGO - Ilhamy, Nabila Fara; Fitriyah, Fitriyah; Hasyim, Muhammad Asmuni (Prodi Biologi Universitas PGRI Ronggolawe, 2025)
Indonesia is a maritime country with abundant marine resources. One type of fish processed product typical in Probolinggo Regency is smoked Lisong Cod Fish. Smoked fish is a processed fish product that uses preservation techniques through smoking. Improper food processing can have negative effects, such as the presence of bacteria in processed products. Several studies still find contamination in processed smoked fish products. Some studies still find contamination in smoked fish processed products. This occurs due to the lack of traders in paying attention to hygiene and sanitation aspects. One of the bacteria related to hygiene and sanitation is Salmonella sp. One of the standards for contamination in processed smoked fish is microbiologically using SNI parameter Number 2725.1 of 200, Salmonella sp. with a negative value/25 grams. This study used smoked cod fish sold at the location of the Probolinggo Regency Smoked Fish Center, This study used smoked tuna (tongkol lisong) sold at the Smoked Fish Center in Probolinggo Regency, with five random locations. One sample of fish was taken from the gills and meat. The data obtained in the form of Salmonella sp. agin 10 samples that had been biochemically tested were then analyzed using SNI 2725.1 of 2009 concerning Smoked Fish Microbiology Standards. The results obtained from the study showed that there was no Salmonella sp. contamination in all samples, but Shigella sp contamination was detected in the A2 sample which was then re-identified using biochemical tests.